The Impact of Green Finance on Carbon Emissions Based on Fixed Effects Model - Wen Tu; Qing Ma; Xin Zhao; Wen Liu (IEEE Access)
During the 14th Five Year Plan period, China will focus on carbon reduction. Green finance has become the main driving force for energy conservation. To explore how green finance affects carbon emissions, a fixed effects model is used for empirical analysis, with the Green Finance Development (GFD) as the explanatory variable, total carbon emissions as the dependent variable, and per capita GDP, technological innovation, industrial structure, environmental protection intensity, and foreign investment level as control variables. Two hypotheses are verified. Firstly, industrial carbon emissions can be significantly declined by improving the GFD. Secondly, the heterogeneity existed in the impact of GFD on industrial carbon emissions across various regions and industries. In the bidirectional fixed effects model regression analysis, the GFD was -0.923, the coefficient of industrial structure optimization was -0.563, and the coefficient of environmental protection was -0.896, all of which were adversely associated with total industrial carbon emissions. In heterogeneity analysis, the GFD had the greatest impact on the eastern region, succeeded by the eastern region, and finally the western region. The GFD is adversely associated with the total industrial carbon emissions, and there is heterogeneity between these two in different regions and industries, providing important empirical evidence for policy makers.